Tax policy and income inequality in the US, 1978 - 2009: A decomposition approach - Olivier Bargain; Mathias Dolls; Herwig Immervoll; Dirk Neumann; Andreas Peichl; Nico Pestel; Sebastian Siegloch (Institute for the Study of Labor (IZA), 2011)
We assess the effects of U.S. tax policy reforms on inequality by applying a new decomposition method that allows us to disentangle mechanical effects due to changes in pre-tax incomes from direct effects of policy reforms. While tax reforms implemented under Democrat administrations, in particular the EITC reforms in the 1990s and the ARRA in 2009, had an equalizing effect at the lower half of the distribution, the disequalizing effects of Republican reforms are due to tax cuts for high-income families. As a consequence of partisan politics, overall policy effects almost cancel out over the whole time period.
urn:nbn:de:101:1-201108173942
Keywords: H23; H31; H53; P16; 330; tax policy; inequality; redistribution; political economy; Great Recession